THE STUDY OF GENETIC VARIABILITY IN ASSOCIATION WITH ZINC UPTAKE EFFICIENCY IN Triticum aestivum L GENOTYPES (Proceedings of International Conference on BioScience and Biotechnology, 2018)
Diversity in agro ecosystems can improve the sustainability of cropping systems in terms of low external inputs and unpredictable climate changes. Agricultural ecosystems in the world are widely related to economical and social status. The major aim of agricultural ecosystems management is to maximize nutrient flow and human service materials. Nutrient efficiency in wheat is very complex. It includes nutrient acquisition efficiency and nutrient use efficiency. In this study 26 winter wheat genotypes were used to investigate the interactive effects between genotypes and the use efficiencies of the Zn micronutrient of the grain. An experiment was carried out in Agricultural and Natural Resources Research and Education, Center of West Azerbaijan, in which Genotypes were planted in complete randomized block design with three replications. The traits such as plant height, biological and grain yield, harvest index, length of spike, number of kernel per spike, thousand kernel weight and spike weight  were measured or calculated. Concentration of Zn in the grain was measured by dry combustion using Perkin Elmer 2380 Atomic Absorption Spectroscopy. Zinc uptake was calculated by multiplying grain Zn concentration in the grain yield. It was revealed that biomass weight of whole plot, plant height, number of kernel per spike, grain yield of main culms, biological yield, length of spike and number of spikelet/spike were positively correlated with grain yield, while the grain protein percentage was negatively correlated with the grain yield. Variance analysis showed that there were highly significant differences among traits. The results obtained in this study indicate that nutrient use efficiency of the Zn varies widely within wheat genotypes. Some genotypes were identified as being Zn use efficiency. These are considered as low-input genotypes. It seems that a special breeding programmer of crop cultivars for low Zn nutrient and stress condition could be successful. Improving the cultivar response to Zn nutrient will help to reduce inputs and hence protect the environment.
Keywords: Wheat; Zn use efficiency; Genetic variability; low input